Kedudukan Nikah Siri,Talak Siri, dan Nikah Online dalam Perspektif Hukum Islam dan Hukum Positif Indonesia - Nurfadilah N; Misbahuddin M; Muhammad Suhufi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the status of unregistered marriages (nikah siri), unregistered divorces (talak siri), and online marriages from the perspective of Islamic law and Indonesian positive law. These three phenomena emerge as forms of marriage and divorce practices that do not fully comply with state law, although some are considered valid according to Sharia. The study used a qualitative method with a normative-juridical approach through analysis of literature, laws and regulations, and Islamic legal perspectives. The findings indicate that unregistered marriages (nikah siri) and unregistered divorces (talak siri) are valid according to religion, but lack legal force before the state because they are not officially registered. Online marriages have sparked debate regarding the validity of the contract, guardians, and witnesses, thus creating legal uncertainty. The impact of these practices is weak protection of women's and children's rights and the potential for legal disputes. This research is useful for providing a more comprehensive understanding of the importance of registering marriages and divorces to ensure legal certainty and protection in family life in Indonesia.